Spatial Distribution and Determinants of Early Marriage among Married Women in Ethiopia: A spatial and Multilevel Analysis - Adugnaw Zeleke Alem; Yigizie Yeshaw; Sewnet Adem Kebede; Alemneh Mekuriaw Liyew; Getayeneh Antehunegn Tesema; Chilot Desta Agegnehu; Achamyeleh Birhanu Teshale (BMC, 2020)
Abstract Background Early marriage is a global public health problem that is mainly practiced in South Asia, Latin America, and sub-Saharan Africa including Ethiopia. It raises the risk of early childbearing of women, higher rates of divorce, and an increased risk of maternal and child death. However, little is known about the spatial distribution and determinants of early marriage in Ethiopia. Therefore, this study aimed to assess the spatial distribution and determinants of early marriage among ever-married women in Ethiopia. Methods A detailed analysis of the 2016 Ethiopian Demographic and Health Survey data was conducted. A total weighted sample of 11,646 reproductive-age married women were included in the analysis. To identify significant hotspot areas of early marriage the Bernoulli model was fitted using SaTScan version 9.6 software. Additionally, to explore the spatial distributions of early marriage across the country ArcGIS version 10.1 statistical software was used. For the determinant factors, the multilevel logistic regression model was fitted. Deviance was used for model comparison and checking of model fitness. In the multivariable multilevel analysis, Adjusted Odds Ratio (AOR) with 95% CI was used to declare significant determinants of early marriage. Results The finding of this study revealed that the spatial distribution of early marriage was significantly varied across the country with Global Moran's I = 0.719 and p value < 0.001. The primary clusters were detected in Tigray, Amhara, and Afar regions. Both individual and community-level factors were associated with early marriage. Having no formal education (AOR = 4.25, 95% CI 3.13-5.66), primary education (AOR = 3.37, 95% CI 2.80-4.92), secondary education (AOR = 1.75, 95% CI 1.32-2.33), and a decision made by parents (AOR = 1.88, 95% CI 1.68-2.09) were individual-level factors associated with higher odds of early marriage. Among the community-level factors, the region was significantly associated with early marriage. Thus, living in Afar (AOR = 1.82, 95%CI 1.37-2.42), Amhara (AOR = 1.77, 95% CI 1.38-2.77), and Gambela (AOR = 1.44, 95% CI 1.09-190) was associated with higher odds of early marriage. Whereas, living in Addis Ababa (AOR = 0.50, 95% CI 0.36-0.68) was associated with a lower chance of early marriage. Conclusion The spatial distribution of early marriage was significantly varied in Ethiopia. Women's education, women's autonomy, and region were found to be the significant determinants of early marriage. Therefore, public health interventions targeting those identified significant hotspot areas of early marriage are crucial to reduce the incidence of early marriage and its consequence. In addition, enhancing women's education and empowering them to make their own choices are vital for changing the customs of the community and eliminating early marriage in Ethiopia.